PELATIHAN KEWIRAUSAHAAN MELALUI PENDAMPINGAN SKILL PEMBUATAN RICE ANCHOVHY CRISPY (RICHOPY) BAGI SISWA DI SMK PGRI PASIR SAKTI LAMPUNG TIMUR - Reni Diah Setiowati; Denny Kurniawan; Robi Santoso (CV SWA Anugerah, 2023)
Pasir Sakti District is one of the sub-districts in East Lampung Regency and administratively consists of 8 villages, namely Pasir Sakti Village, Mekarsari Village, Mulyosari Village, Rejomulyo Village, Purworejo Village, Kedung Ringin Village, Sumur Tikus Village and Labuhan Ratu Village. People in this sub-district work as rice farmers and fishermen and many also work as fish farmers in ponds whose main commodities are shrimp and milkfish. One of the catches from fishermen in this area is anchovies or often called anchovies. And in certain seasons, the catch of anchovies can reach tens of quintals in one day of fishing. With this abundant catch, most people or fishermen only sell it in wet and dry form without carrying out further processing which has high economic value. The service team sees that there is a great opportunity to utilize this large source of raw materials, namely by processing rice anchovies into other goods that have higher economic value which can provide better results for the welfare of the community who want to jointly develop rice anchovy processing. the. Students at Vocational High Schools or abbreviated as SMK PGRI Pasir Sakti, who generally have the paradigm that when they graduate from school they have to work in a certain place, need to change their mindset so that they are willing to try to independently produce something, not just through working as workers. . So the service team plans to carry out entrepreneurship development training, especially for prospective graduates of SMK PGRI Pasir Sakti and generally all parties in the school and the surrounding community, namely by making or processing rice anchovies into crispy rice anchovies (Rice Anchopy Crispy) or abbreviated as